1993
DOI: 10.1177/106591299304600414
|View full text |Cite
|
Sign up to set email alerts
|

Citizens' Contacts with Bureaucratic and Legislative Officials

Abstract: This paper draws on both the bureaucratic and congressional literature to develop and test a model linking bureaucratic dissatisfaction with citizen- initiated contact with members of Congress. It has been argued by Fiorina and others that bureaucratic malfunctioning creates opportunities for congressional intervention which aids constituents and reaps electoral benefits for elected representatives. While this view has been widely accepted by scholars, empirical research has scarcely addressed the question, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
1
11
0
1
Order By: Relevance
“…Finally, prior research also is marred by occasional "groping" for indicators, that is, by efforts to find indicators where they may not exist. Education, for example, has been used as a measure of awareness (Serra 1995;Moon, Serra, and West 1993). One might expect education to be related to awareness, but there is no more basis for assuming an identity between the two than there is for assuming an identity between objective needs and perceived needs.…”
Section: What Scholars Have Done Wrong: Measurement Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, prior research also is marred by occasional "groping" for indicators, that is, by efforts to find indicators where they may not exist. Education, for example, has been used as a measure of awareness (Serra 1995;Moon, Serra, and West 1993). One might expect education to be related to awareness, but there is no more basis for assuming an identity between the two than there is for assuming an identity between objective needs and perceived needs.…”
Section: What Scholars Have Done Wrong: Measurement Problemsmentioning
confidence: 99%
“…Sharp (1986, 100), for example, has found that involvement with neighborhood organizations helped to explain citizen-initiated contacts in Kansas City, Missouri. Other researchers have identified other kinds of local political or civic involvements as significant factors, with those citizens who are more socially and politically involved more likely to initiate contacts (e.g., Moon, Serra, and West 1993;Hirlinger 1992;Peterson 1988).…”
Section: Other Social And/or Political Involvementmentioning
confidence: 99%
“…We focus on citizen-initiated contact. Moon, Serra, and West (1993) argued that to understand contact, we must first understand who is contacted and thus draw a distinction between bureaucrats and other government representatives, such as parliamentarians and representatives of localities. Moon, Serra, and West's (1993) excellent suggestion is hampered by vagueness on who counts as a "public official."…”
Section: Definition Of Contact As a Form Of Participationmentioning
confidence: 99%
“…In the course of receiving the public, all the problems of human existence (or almost all) are liable to be broached by the people who telephone, come to see or contact their deputy by letter or E-mail. Classically, complaining about bureaucracy is the primary reason that causes people to contact a legislative official (Moon et al, 1993). Next to parents' requests for permission to register their child in a school outside their sector, 9 civil servants applying for transfers or tenure, people wanting to receive a decoration, future retirees unhappy with the way their pension was calculated, citizens protesting about public services shutting down (maternity wards, schools, classes, etc.…”
Section: "Treating" Demands In a District: Regulation Strategiesmentioning
confidence: 99%